The Influence of Good Corporate Governance and Company Size on Company Financial Performance: Empirical Study on Banking Companies Listed on the Indonesia Stock Exchange 2019-2022 - Bellen, Atalya; Muktiadji, Nusa; Pardede, Robert Pius (Institut Bisnis dan Informatika Kesatuan, 2025)
Bank companies are one of the sectors that encourage the pace of Indonesian economic growth. In order to run its business, banks are required to implement good corporate governance to minimize aberrations that might impact the company's financial performance. The Board of directors, ownership structure, and firm size are some of the most important parts of maintaining the bank business through the good corporate governance mechanism. This research was conducted to analyze and to study the influence of the size of the board of directors, institutional ownership, managerial ownership, and firm size on the company's financial performance that is projected on return on assets, where an empirical study was carried out on banking companies listed on the Indonesian Stock Exchange for the 2019-2022 period. The sample for this research came from 22 companies that met the purposive sampling criteria, where the companies were multiplied by 4 periods to obtain 88 samples. The results of this research show that partially, there is an influence of institutional ownership on financial performance. In contrast, the size of the board of directors, managerial ownership, and firm size have no partial effect on financial performance. Then for simultaneous testing, there is the influence of good corporate governance (board of director size, institutional ownership, managerial ownership), and firm size on financial performance. Keywords: Good Corporate Governance, Board of Director Size, Institutional Ownership, Managerial Ownership, Firm Size, Return On Assets